2010
DOI: 10.4141/cjps09027
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer response for hybrid and open-pollinated canola and economic optimal nutrient levels

Abstract: . 2010. Fertilizer response for hybrid and open-pollinated canola and economic optimal nutrient levels. Can. J. Plant Sci. 90: 305Á310. Hybrid (HY) canola (Brassica napus L.) produces a higher seed yield than open-pollinated (OP) canola. While it is expected higher-yielding HY canola may require higher total available nutrients, especially nitrogen (N), the evidence is not conclusive. This study used canola yield data from several site-years and fertility experiments to determine whether HY and OP canola types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The cited earlier studies of spring-planted canola tested open-pollinated varieties, which have been shown to have considerably lower yield potential and fertilizer requirements than currently grown hybrids (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010). The cited earlier studies of spring-planted canola tested open-pollinated varieties, which have been shown to have considerably lower yield potential and fertilizer requirements than currently grown hybrids (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010).…”
Section: Yield Response To Early Defoliation In Spring-planted Canolamentioning
confidence: 99%
See 2 more Smart Citations
“…The cited earlier studies of spring-planted canola tested open-pollinated varieties, which have been shown to have considerably lower yield potential and fertilizer requirements than currently grown hybrids (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010). The cited earlier studies of spring-planted canola tested open-pollinated varieties, which have been shown to have considerably lower yield potential and fertilizer requirements than currently grown hybrids (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010).…”
Section: Yield Response To Early Defoliation In Spring-planted Canolamentioning
confidence: 99%
“…C anola is an important revenue crop in the northern Great Plains of North America, where it is cultivated on over 8 million hectare in Canada and 0.7 million hectare in the United States (Statistics Canada, 2014;USDA, 2014). Producers grow hybrid varieties with high seeding and fertilizer rates that maximize seed yield and economic potential (Karamanos et al, 2005;Brandt et al, 2007;Smith et al, 2010). Despite producers' best efforts, however, canola, like all crops, is susceptible to environmental stressors, such as hail, that may partially or fully defoliate the crop.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Canola requires high levels of N to optimize yield (Grant and Bailey, 1993; Malhi and Gill, 2004; Karamanos et al, 2005). Virtually all of the canola now grown in western Canada consists of hybrid varieties that may require an even higher N supply than open‐pollinated varieties to support their higher yield potential (Malhi et al, 2007; Cutforth et al, 2009; Smith et al, 2010; Blackshaw et al, 2011; Harker et al, 2012). As well as being costly to canola producers, applying large amounts of fertilizer N can have negative environmental effects (Henault et al, 1998; Cassman et al, 2002; Gan et al, 2011a, 2011b) and energy use efficiency (Zentner et al, 2004) impacts.…”
mentioning
confidence: 99%
“…In 2015, most continuous canola yield increases compared with SP occurred as a result of additional fertilizer or fungicide (Table 5). Other studies have confirmed canola yield responses to N (Cutforth et al 2009;Smith et al 2010;Blackshaw et al 2011;Harker et al 2012;O'Donovan et al 2014) or fungicides (Kutcher and Wolf 2006;Harker et al 2012), but those studies were not continuous canola. At Beaverlodge, yield increased relative to SP in every treatment that included a higher fertilizer rate.…”
Section: Canola Seed Yieldmentioning
confidence: 97%